(untitled) (Iraqi Journal of Medical Sciences, 2016)
Background: Myoepithelial cells play an important role in the interpretation of breast fine needle aspiration cytology, since these cells are believed to be a component of the benign process in the breast lesion. Myoepithelial cells distinction may be difficult occasionally, so their demonstration by immunocytochemistry method through myoepithelial cell marker like smooth muscle actin is a useful diagnostic tool to differentiate between benign and invasive malignant lesions. Objective:To study the role of smooth muscle actin as immunocytochemical marker in the demonstration of myoepithelial cell as an aid in the diagnosis of benign breast lesions in fine needle aspiration cytolog of breast. Methods:Forty five cases of fine needle aspiration cytology of palpable female breast lesions were selected. 25 out of these 45 cases comprised 20 invasive breast carcinoma and 5 fibrocystic diseases with atypia stained with smooth muscle actin by immunocytochemistry method directly and 20 cases comprised of 10 fibroadenoma and 10 fibrocystic disease stained with smooth muscle actin after destaining from H&E stain. All of these cases had a confirmatory histological diagnosis. Results:Smooth muscle actin staining consistently highlighted the myoepithelial cells in smears of all histologically proven benign lesions such as fibroadenomas and fibrocystic changes. In contrast, invasive breast cancers demonstrated absence of staining with smooth muscle actin that seen in benign breast lesions. Conclusion:Application of smooth muscle actin immunostaining in breast fine-needle aspirates is feasible and practical. The use of destained H&E smears provides an effective means to directly examine any atypical cluster of cells for the presence of MEC differentiation. The demonstration of presence or absence of MEC differentiation in atypical cases can provide sufficient evidence to decrease error in diagnosis (false positive) of breast fine-needle aspirates. Keywords:Smooth muscle actin, fine needle aspiration cytology, breast lesions